Analisis Kesalahan Berbahasa Dalam Pidato Tokoh Politik Indonesia Masa Bakti 1945-Sekarang Ditinjau Dari Perspektif Linguistik - Shofiyatul Mukromiyah; Alfina Fitriani; Aliza Maula; Evi Fatmalasari; Ai Siti Nurjamilah (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
Language errors often occur consciously because students basically believe that they do not master the language system they use, so they are not sure about the words they make. Because of the difficulties he experienced, he then thought about creating his own language or even abandoning it. This research analyzes language errors from the most important thing, namely the speeches of Indonesian state leaders from the beginning until now. The analysis was carried out using theories viewed from a linguistic perspective, including Phonology, Semantics and Spelling (EYD). We should preserve the Indonesian language by communicating well, politely and courteously so that we as young people do not feel the fading of this language. Additionally, we must reduce the use of slang, especially in conversations on social media, as it can influence the way the next generation speaks. In everyday life, language must be adapted to the situation at hand and spoken correctly.